Data-Driven Bed of Nails Wear Analysis for the in-Circuit-Testing of Electronic Modules - Sindel, Till; Thielen, Nils; Mahr, Felix; Reichenstein, Tobias; Erdogan, Hüseyin; Franke, Jörg (2024 IEEE 29th International Conference on Emerging Technologies and Factory Automation (ETFA), 2024)
In order to optimize the timing of maintenance operations, this work aims at laying the foundation for applying predictive maintenance strategies for the In-Circuit-Test (ICT) by proposing a data analysis pipeline for capturing wear impact on process data. The ICT is an established inspection process within the electronic module production. Subsequently to the assembly of components on a printed circuit board (PCB) mainly using the surface mount technology (SMT) and through hole technology (THT), parts are tested for their conformity of electrical characteristics to predefined tolerances, as well as logical functionalities. Thereby, the ICT is conducted by physically connecting an adapter containing a bed of nails to the circuits of the assembled part and subsequently measuring component dependent characteristics such as the electrical resistance, impedance, inductivity and capacity. Due to the mechanical and electrical impact on the probes and the high-volume nature of the process, these temporarily connected components are subject to wear. Conventional maintenance approaches follow a scheduled preventive strategy by conducting maintenance operations following a predefined number of cycles or strokes. Due to the heuristic nature of the scheduling, the wear margin is not fully exploited and therefore additional costs for prematurely replacing the probes or the complete bed of nails occur. The findings for a real-world dataset from high-volume electronics production show temporal shifts in data distributions between maintenance operations, suggesting adapter-wide needle degeneration. Considering PCB and component batch effects is proposed for successive research methodologies in order to improve the accuracy of the approac